Answer:
(
g
−
f
)
(
a
)
=
g
(
a
)
−
f
(
a
)
(
g
−f
)
(
a
)
=
g
(
a
)
−
f
(
a
)
=
−
3
a
−
3
−
a
2
−
5
=
−
a
2
−
3a
−
8
Step-by-step explanation:
It would be
y=(-16*-1)
which would then be
y=16
so the answer would be
(-16,16)
you replace the x in the equation with the x you are given
Answer:
either diameter or perimeter
Step-by-step explanation:
Answer:
Option 1 is correct that is square root of 18.
Step-by-step explanation:
We will use pythagoras theroem to find the length of hypotenuse
![c^2=a^2+b^2](https://tex.z-dn.net/?f=c%5E2%3Da%5E2%2Bb%5E2)
Here, c is hypotenuse,a is one leg and b is the other leg.
Here, a=b=3
On substituting the values in the formula we get:
![c^2=3^2+3^2=18](https://tex.z-dn.net/?f=c%5E2%3D3%5E2%2B3%5E2%3D18)
![c=\sqrt{18}](https://tex.z-dn.net/?f=c%3D%5Csqrt%7B18%7D)
Hence, Option 1 is correct that is square root of 18.